Determinant Factors of Musculoskeletal Disorders among Technical Service Workers at the State Electricity Company (PLN) of Malang City - Nadia Rosalinda; Anita Sulistyorini (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2026)
Workers are exposed to various occupational hazards that may lead to occupational diseases (ODs), including musculoskeletal pain resulting from work processes, commonly referred to as musculoskeletal disorders (MSDs). Technical service workers at the State Electricity Company (Perusahaan Listrik Negara/PLN) of Malang City are at risk of experiencing MSDs due to manual handling tasks and individual worker characteristics. This study aims to analyze exposure to MSD risk factors. This quantitative study employs a descriptive-analytical approach and involves a total sample of 26 technical service workers. Data were collected through observations and analysed using observation sheets, work posture assessments based on the Ovako Working Posture Analysis System (OWAS), and the Nordic Body Map (NBM) questionnaire to assess MSD complaints. The findings indicate that the key determinants contributing to MSD complaints among workers include work posture, gender, age, body mass index (BMI), and years of service.  Keywords: risk factors, musculoskeletal disorders (MSDs), technical service workers